Curriculum Development in Public Administration to Support the Management of Sharia-Based Tourism Villages - Fitri Pebriani Wahyu; Muhammad Andi Septiadi (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to analyze the needs and develop the curriculum of the Public Administration study program to better support the management and development of sharia-based tourism villages. The findings indicate that the current curriculum remains general and does not fully integrate sharia principles within public administration, making it less effective in preparing graduates with the necessary competencies in this field. The primary challenges identified include a lack of understanding of sharia concepts in public administration, limited expertise among educators, and insufficient reference materials and supporting content related to sharia-based tourism. As a solution, this study proposes a curriculum development model that incorporates sharia principles into public administration courses, practical training, and internship programs in sharia-based tourism villages, as well as continuous training and workshops for students and educators. The implementation of this model is expected to enhance the quality of graduates by equipping them with the skills required to manage and develop sharia-based tourism villages effectively. The successful application of this curriculum requires collaboration among educational institutions, government agencies, and local communities to ensure its effectiveness and sustainability. Thus, the Public Administration program can make a significant contribution to the sustainable and inclusive development of sharia-based tourism villages while supporting broader national development goals.